PERENCANAAN PERKUATAN PERLINTASAN KERETA API SEBIDANG DENGAN MENGGUNAKAN PLAT BETON BERTULANG - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Bhakti Pramadita (Universitas Widyatama, 2023)
lroad track and a motorized highway. Based on data and field reports at railroad crossings with highways, it is often found that damage to the asphalt layer (Surface Coarse). The cause of asphalt damage occurs due to a shift between the ballast gravel under the asphalt surface. Where the asphalt layer should be on a solid pavement or foundation, so that the life of the asphalt surface will be more durable. So to overcome these problems, a comparative study was conducted on the planning of retrofitting of the crossing using reinforced concrete slabs and using used railroad tracks. In the design of the reinforced concrete slab, a plate measuring 3x0.6 meters thick 7 cm with a concrete quality of K-225 (18.68 Mpa) is used which can withstand a train axle load of 18 tons. The load on the used railroad tracks is used by large-loaded vehicles, namely truck loads of 10 tons